Is risk-taking behaviour more prevalent among adolescents with learning disabilities - Palfiova, Michaela; Dankulincova Veselska, Zuzana; Bobakova, Daniela; Holubcikova, Jana; Cermak, Ivo; Madarasova Geckova, Andrea; van Dijk, Jitse P; Reijneveld, Sijmen A (European journal of public health, 2017)
Background: Reports from schools indicate that adolescents with learning disabilities (LD) frequently show risk-taking behaviour (RTB), but evidence is lacking. The aim of the study was to assess the associations between LD status and RTBs among Slovak adolescents and to explore whether family affluence and family composition have a moderating or mediating role in these associations. Data from the Slovak national HBSC study 2014 were analyzed. The sample comprised 1549 15-year-old adolescents (mean age: 15.4; 52.5% boys). RTBs were defined as early sexual experience, truancy, fighting, bullying, early smoking initiation and drunkenness. The associations between LD status and RTBs were assessed using binary logistic regression; the mediating as well as moderating role of family affluence and family composition was explored as well. Adolescents with LD are two times more likely to be engaged in early sexual experiences (OR 2.39; 95% CI 1.45-3.95), fighting (OR 1.72; 95% CI 1.01-2.95) and bullying (OR 2.08; 95% CI 1.26-3.44), but not in early smoking initiation, drunkenness or truancy. Family affluence and family composition did not moderate or mediate these associations. Adolescents with LD are at high risk of early sexual experiences, fighting and bullying but not of smoking initiation, drunkenness or truancy. Non-intact and poor families do not increase the risks associated with LD status of adolescents; however, in these families adolescents with LD are more prevalent.
Keywords: Female; Risk-Taking; Prevalence; šikana; ženské pohlaví; Adolescent Behavior; Adolescent; Slovakia; lidé; Bullying; poruchy učení; Learning Disabilities; Sexual Behavior; sexuální chování; prevalence; Male; mladiství; Slovenská republika; mužské pohlaví; riskování; chování mladistvých; Humans